Mepivacaine reduces calcium transients in isolated murine ventricular cardiomyocytes - Mosqueira, Matias; Aykut, Güçlü; Fink, Rainer (BMC anesthesiology, 2020)
The potential mechanism of mepivacaine’s myocardial depressant effect observed in papillary muscle has not yet been investigated at cellular level. Therefore, we evaluated mepivacaine’s effects on Ca2+ transient in isolated adult mouse cardiomyocytes.